Langerhans Cells Closely Associated with Thy-1-Positive Dendritic Cells in the Stratified Squamous Mucosal Epithelium of Mice - NIWA, Jun-ichi; KOBAYASHI, Miya; KOYAMA, Yoh-ichi; KOTANI, Hisanari; MITSUDO, Kenji; HOSHINO, Takeshi (Archives of histology and cytology, 1994)
An immunohistochemical study was carried out on two types of dendritic immune cells, Langerhans cells and Thy-1-positive cells, in the epithelium of the forestomach of 1-, 2-, 3-, 4- and 8-week-old mice. Investigation focused on how both types of cells were distributed and might interact in the mucosal epithelium. Langerhans cells and Thy-1-positive dendritic cells appeared in mucosal epithelium at 3 weeks of age, while in the epidermis they were first observed just after birth. In contrast with the epidermal Thy-1-positive cells, mucosal Thy-1-positive cells were closely associated with Langerhans cells. Electron microscopy also confirmed that two types of immune cells interact directly in the stratified squamous mucosal epithelium of mice.